Communications and information infrastructure security - Voeller, John G. (Wiley, 2014)
Communication and Information Systems Security features articles from the Wiley Handbook of Science and Technology for Homeland Security covering strategies for protecting the telecommunications sector, wireless security, advanced web based technology for emergency situations. Science and technology for critical infrastructure consequence mitigation are also discussed.